Managing multinationals in a knowledge economy economics, culture, and human resources - Cheng, Joseph L. C. 1952-; Hitt, Michael A. (Elsevier JAI, 2004)
This volume includes contributing chapters from authors based in Asia, Europe, and North America to examine an emerging topic in the international management field - managing multinationals in a knowledge economy. They were selected to reflect the influences of three key factors - economics, culture, and human resources - on managerial decisions that affect multinationals and their effective operations. Leading the volume is an invited article by John H. Dunning, "An Evolving Paradigm of the Economic Determinants of International Business Activity." It presents a comprehensive review of his thirty-plus years of research on the eclectic paradigm, and a preview of his most recent work on the role of relational and institutional assets in foreign direct investment.This article, along with commentaries on Dunning's work written by Jose de la Torre, Timothy Devinney, Will Mitchell, and Stephen Tallman, can be found in the Research Forum section. The present volume also includes five other articles selected through a double-blind review process. They complement the Research Forum papers, which focus on the economic determinants of international business activity, by examining critical cultural and human resource issues faced by multinationals.These include: the role of culture in entry mode decisions, the impact of national context on top management teams, cultural attributes of Russian management, the utilization of managerial expatriates, and the bridging of theory and practice in international human resource management research. A review of the volume's ten chapters suggests that, despite all the technological advances in cross-border communication and coordination, social capital and human resources are the most critical factors possessed by multinationals.
Keywords: International business enterprises -- Management.; Knowledge management.; Corporate culture.; elektronické knihy; electronic books